Development and validation of the sedentary behavior regulation scale in Korean Adults Population - Mi Hwa Won; Sun-Hwa Shin (PLoS ONE, 2026)
Sedentary behavior is a well-established independent risk factor for numerous chronic diseases. However, validated tools to assess the psychological and behavioral regulation of sedentary time remain limited. This study aimed to develop and validate a self-report scale for assessing sedentary behavior regulation in Korean adults. This scale was developed using a comprehensive multiphase process. First, items were generated based on a comprehensive literature review and expert consultation, followed by a content validity assessment. In total, 600 Korean adults were recruited. Construct validity was examined using exploratory factor analysis (EFA) and confirmatory factor analysis (CFA). Criterion validity was evaluated by assessing the correlation between the new scale and the Global Physical Activity Questionnaire (GPAQ). Finally, reliability was assessed through internal consistency and test-retest reliability. The final instrument, the Sedentary Behavior Regulation Scale (SBRS), consisted of 12 items across two distinct sub-factors: sedentary behavior management and environmental support and active movement in sedentary contexts. Criterion-related validity was supported by a small but significant positive correlation with physical activity (r = .19, p < .001) and a small to moderate negative correlation with sedentary time (r = −.33, p < .001). The scale also exhibited excellent internal consistency (Cronbach’s α = .87, McDonald’s omega = .87) and good test-retest reliability (intraclass correlation coefficient [ICC] = .85). Overall, the SBRS demonstrated preliminary evidence of reliability and validity for assessing behavioral and environmental strategies to reduce sedentary time. This study advances our understanding of sedentary behavior beyond simple activity measurements and provides a valuable foundation for developing targeted public health interventions to mitigate sedentary time.